HUBUNGAN ANTARA PENGUASAAN VOCABULARY DENGAN READING ABILITY PARA KARYAWAN PT. AMMI BOGOR - Ika Chairiyani (Jurnal TEDC, 2015)
Many job fields which relate with English language include announcement, business letter or correspondence which must be read and understood by employees, but not all of the employees can comprehend them because of the lack of vocabulary. The relationship between vocabulary mastery and English reading ability of the employees at PT AMMI Bogor, with the respondents are 30 person from 118 employees. The research methodology used is descriptive method by data collecting technique through test distribution, field observation and literature study. The data management using correlation analysis statistic. The result of the research shows that there is a significant relationship between vocabulary mastery and English reading ability of the employees at PT AMMI Bogor. This research is suitable with education curriculum about announcement and letter reading and vocabulary teaching of the tenth grade at senior high school. Keyword : Strategi Bauran Promosi, Strategi Bauran Produk dan Keputusan Konsumen.